2009
DOI: 10.1016/j.jmb.2009.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Small Peptides, Inhibitors of Translation

Abstract: Identification of small molecular weight compounds targeting specific sites in the ribosome can accelerate development of new antibiotics and provide new tools for ribosomal research. We demonstrate here that antibiotic-size short peptides capable of inhibiting protein synthesis can be selected by using specific elements of ribosomal RNA as a target. The ‘h18’ pseudoknot encompassing residues 500-545 of the small ribosomal subunit RNA was used as a target in screening a heptapeptide phage display library. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Related studies that were reported recently reveal similar results (52). The limitation of using phage display to screen peptides that specifically interfere with protein synthesis of bacteria is that the strongest binders may not actually be selected because the host E. coli would not survive, therefore failing to amplify the phage bearing the infused peptide.…”
Section: Discussionsupporting
confidence: 87%
“…Related studies that were reported recently reveal similar results (52). The limitation of using phage display to screen peptides that specifically interfere with protein synthesis of bacteria is that the strongest binders may not actually be selected because the host E. coli would not survive, therefore failing to amplify the phage bearing the infused peptide.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, macrolide binding seems to be involved in cellular processes. Thus, stalling by specific nascent peptides, a cellular mechanism used for regulation of expression of several bacterial and eukaryotic genes, is sensitive to signals connected with macrolide binding (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83).…”
Section: Figurementioning
confidence: 99%
“…Examples are those used recently to target Helix 69 (111), the first 16 residues of the proline-rich antimicrobial peptide mammalian Bac7 (112), the thiazolyl peptide antibiotics (113), and the small peptides that were shown to inhibit translation in prokaryotes (75,114).…”
Section: Figurementioning
confidence: 99%
“…This seemingly simple process could be assisted by other molecules acting as small chaperones [35] offering stabilization. Additional structural support could be obtained from short peptides that have high affinity for RNA [36], or from longer poly-amino acids, similar to protein-RNA interactions within the contemporary ribosome, or from interactions of low-molecular-mass compounds with exposed regions of RNA. These short peptides could have been produced by uncoded elongation by early versions of the proto-ribosome or by other means.…”
Section: Emergence Of the Proto-ribosomementioning
confidence: 99%